PATHOMORPHOLOGICAL CHANGES IN NEONATES WITH HYALINE MEMBRANE DISEASE (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
To develop and improve the criteria for pathomorphological changes in the lungs of neonates with hyaline membrane disease.